KOMPETENSI MAHASISWA JURUSAN AKUNTANSI DAN KESIAPANNYA DALAM MENGHADAPI DUNIA KERJA ERA MASYARAKAT EKONOMI ASEAN (MEA ) - Wirianata, Henny (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2017)
The objective of this research is to know accounting student’s competency andtheir readiness to enter working environment in ASEAN Economic Community (AEC) era. Accounting student’s competency measured by ethical competency, knowledge competency, capability competency, relationship competency, and analysis competency. This research used primary data from questionnaires given to Tarumanagara University accounting students as respondents. The result of this research showed that Tarumanagara University accounting students have adequate ethical, capability, relationship, and analysis competency, but still not adequate for knowledge competency. Ethical, knowledge, and capability competency have significant influences to accounting student’s readiness, while relationship and analysis competency have insignificant influences to accounting student’s readiness to enter working environment in AEC era.